Electronic instruments and measurements - Jones, Larry D.; Chin, A. Foster (New Jersey : Prentice-Hall, 1991)
Designed to teach students how to select electronic instruments and interpret their readings to get accurate, reliable and cost-effective measurements. The authors present the basic theory of the operation of both DC and AC instruments, their capabilities and limitations.
Keywords: ELECTRONIC INSTRUMENTS